Compact, Hybrid III-V/Silicon Vernier Laser Diode Operating From 1955–1992 nm - Jia Xu Brian Sia; Xiang Li; Wanjun Wang; Zhongliang Qiao; X. Guo; Jiawei Wang; Callum G. Littlejohns; Chongyang Liu; Graham T. Reed; Kian Siong Ang; Hong Wang (IEEE Photonics Journal, 2021)
The 2 µm waveband is capable of enabling pervasive applications. The demonstration of the hollow-core photonic bandgap fiber and the thulium-doped fiber amplifier has highlighted the fiber propagation and amplification aspects of fiber communications, indicating its potential as an adjunct to present communication infrastructure at the O/C bands. The above is especially imperative given the current concerns with regards to the upper bandwidth limit of the single-mode fiber. Furthermore, the waveband could facilitate many more applications such as LIDAR and free-space communication. However, water absorption (OH-) is high at most of the 2 μm waveband and this will impact the optical insertion loss of applications implemented in the wavelength region. The relative low water absorption region of the waveband falls within 1950 – 2000 nm. As such, the development of a hybrid/heterogeneous III-V/silicon laser source that operates within the region is important for 2 µm silicon photonics. In this work, we demonstrate a III-V/Si hybrid tunable laser operating from 1955 - 1992 nm for the first time. Room temperature continuous wave operation is achieved with a maximum laser output power of 8.1 mW. This wavelength-tunable laser operates specifically within the low water absorption window, indicating good wavelength suitability for applications at the 2 μm waveband.